ANALISIS KANDUNGAN GIZI DAN UJI ORGANOLEPTIK PADA BAKSO TEMPE DENGAN PENAMBAHAN DAUN KELOR (Moringa oleifera) - Hasniar, Hasniar; Rais, Muhammad; Fadilah, Ratnawaty (Universitas Negeri Makassar, 2019)
This study aims to determine the effect of adding Moringa leaves to the nutritional content and acceptability of panelists on tempeh meatballs. This research is an experimental study using a completely randomized design (CRD) with the concentration of addition of Moringa leaves 2%, 4% and 6%. Observation parameters; Water content, ash content, protein, fat, carbohydrate, calcium, beta-carotene, with a panelist test of color, texture, taste and aroma. The results showed that the best treatment was aimed at the treatment of adding 4% Moringa leaves to the panelists in terms of color, texture, taste and aroma with moisture content 65.21%, ash content 1.59%, protein content 9.46%, fat content 0.88%, carbohydrate content 24.19%, 890 mg calcium levels, and beta-carotene levels 756 Âµg/g and meet quality standard requirements (SNI 01-3818-1995).